Full-biodegradable film as well as preparation method and application thereof
The fully biodegradable film prepared by multi-layer coextrusion technology uses polyester materials modified with polyvinyl alcohol and epoxy modifiers to solve the problem of insufficient adhesion of existing films and achieve efficient and environmentally friendly packaging effects.
Patent Information
- Application Number
- CN202411915896.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The existing polyethylene films are insufficiently bonded when packaging metal or frosted ceramics, glass and other materials, resulting in high costs, difficult to remove glue residues, release of toxic volatile substances, and undegradable materials, causing environmental pollution.
A fully biodegradable film is prepared by multi-layer co-extrusion technology. The inner layer uses materials such as polyvinyl alcohol and plasticizers. The outer layer is a polyester fully biodegradable material modified by epoxy modifiers. Through the properties of wetting and tackiness, it achieves a close fit with building materials.
It solves the problem of insufficient adhesion, reduces costs, is easy to remove, is non-toxic and environmentally friendly, and the film can be degraded, reducing environmental pollution.
Smart Images

Figure CN119898102A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a fully biodegradable film and a preparation method and application thereof. Background Art
[0002] Common materials such as glass, tiles, and wood are hard in texture, and some surfaces have been polished, frosted, electroplated, painted, etc. During transportation, it is necessary to prevent the surface of the materials from being bumped, scratched, and scratched. Packaging materials such as foam boards, cardboard, and plastic films can protect these building materials very well and are often used in building material packaging. Among them, plastic films have the characteristics of good adhesion, high transparency, small volume, light weight, thin thickness, flexibility, and not easy to break compared to other packaging materials. As a packaging material for building materials, they are widely used.
[0003] Common polyethylene films can be tightly attached to smooth glass and tile surfaces through electrostatic adsorption. However, when used on metal materials or frosted ceramic, glass and other material surfaces, glue is often applied to the polyethylene film surface in order to improve the adhesion between the film and the packaged material. This will bring a series of problems: (1) In order to ensure the strength of the film so that it can be torn off the packaged material, the thickness of this PE film is often up to 30 microns, which increases the cost of use; (2) The glue used is often insoluble in water. After the film is removed, the glue may remain on the surface of the packaged material and become dirt that is difficult to scrub off; (3) The glue may contain toxic volatile substances such as formaldehyde, which can be easily released into the environment and cause harm; (4) Polyethylene material cannot be degraded, and large-scale use will cause environmental damage. Summary of the invention
[0004] The invention provides a fully biodegradable film and a preparation method and application thereof. Polyvinyl alcohol and polyester fully biodegradable materials are made into an inner and outer double-layer film by a melt extrusion method. The polyvinyl alcohol in the inner layer has adhesiveness in a wet state and can adhere to the surface of building materials after being wetted. It is not easy to tear after drying, and the adhesive layer and the structural layer are not easy to peel off, thereby solving the problems of high cost, difficulty in removal and difficulty in degradation caused by the sizing treatment in the prior art.
[0005] The present invention is achieved through the following technical solutions:
[0006] A fully biodegradable film is a multi-layer co-extruded film with an inner and outer two-layer structure. The outer layer is a polyester fully biodegradable material modified by an epoxy modifier; the inner layer is a mixed material. Based on the total weight percentage of 100%, the raw materials of the inner layer mixed material include 50-90% polyvinyl alcohol, 5-20% plasticizer, 1.5-8% ethylene-acrylate-glycidyl methacrylate, and the rest are other additives. The other additives are selected from one or more of antioxidants, opening agents, and inorganic powder fillers. The polyvinyl alcohol has an alcoholysis degree of 78-99% and a polymerization degree of 30,000-170,000.
[0007] Preferably, the inner layer further comprises a polyester-based fully biodegradable material modified by an epoxy-based modifier, which accounts for no more than 30%.
[0008] Preferably, the polyester fully biodegradable material modified by the epoxy modifier is modified by modifying the polyester fully biodegradable material with the epoxy modifier having a raw material weight ratio (compared to the outer layer weight ratio) of 0.4-0.8%; the polyester fully biodegradable material is selected from one or two materials of polybutylene adipate / terephthalate, polylactic acid, polypropylene carbonate, polybutylene succinate, polyglycolic acid, and polycaprolactone. The polyester fully biodegradable material includes a filling material with the polyester biodegradable material as the main material.
[0009] Preferably, the epoxy modifier is an epoxy chain extender.
[0010] Preferably, the epoxy modifier is an oligomer with a molecular weight of 6000-8000 g / mol and an epoxy value of 200-400 g / mol.
[0011] When the present invention uses a high-temperature water-soluble film with an alcoholysis degree of 99%, it will not become sticky in normal temperature water and will not be washed away by a large amount of water. Only in high-temperature hot water above 80°C will the inner layer become sticky and be washed away by a large amount of hot water. Preferably, the alcoholysis degree of the polyvinyl alcohol is 78-88%, and further 88%. At this time, the film can be thickened by a small amount of water at room temperature or washed away by a large amount of water.
[0012] Preferably, the plasticizer is glycerol. The present invention can also use a composite plasticizer mainly composed of glycerol and other plasticizers. Other plasticizers include but are not limited to one or more polyol materials such as ethylene glycol, polyethylene glycol, triethylene glycol, 1,3-propylene glycol, etc.
[0013] Preferably, the weight proportion of glycidyl methacrylate groups in the ethylene-acrylate-glycidyl methacrylate is 6-10%.
[0014] The method for preparing the fully biodegradable film is prepared by heating, melting and multi-layer co-extrusion, and the film is prepared by film blowing, casting and calendering.
[0015] Specifically, the steps of preparing a fully biodegradable film by film blowing method are as follows:
[0016] (1) Weighing a polyester fully biodegradable material and an epoxy modifier by weight, melt-blending them in a twin-screw extruder, extruding them into granules, and drying them to obtain a polyester fully biodegradable material modified with an epoxy modifier as an outer layer material;
[0017] (2) weighing the inner layer raw materials, fully mixing polyvinyl alcohol, plasticizer and other additives in a high-speed stirrer, melt blending in a twin-screw extruder, and then mixing with ethylene-acrylate-glycidyl methacrylate at room temperature at high speed to obtain the inner layer material;
[0018] Alternatively, the raw materials are weighed by weight, polyvinyl alcohol, the polyester-based fully biodegradable material modified by the epoxy modifier obtained in step 1), a plasticizer and other additives are fully mixed in a high-speed mixer, melt-blended in a twin-screw extruder, and then mixed with ethylene-acrylate-glycidyl methacrylate at room temperature at high speed to obtain an inner layer material;
[0019] (3) The outer layer material and the inner layer material are respectively added into a double-layer extrusion film blowing machine, and the film is blown, the edges are cut, and the packaging film is rolled up.
[0020] The present invention also provides the use of the above-mentioned fully biodegradable film in the packaging of building materials, wherein the inner layer of the film faces the building materials and is in direct contact with the building materials.
[0021] Preferably, the building material is tile or glass.
[0022] The fully biodegradable film of the present invention is sticky when wet. The film has an inner and outer two-layer structure, the outer layer is facing away from the packaged material, and the inner layer is facing the packaged material and in direct contact with the packaging material. After the surface of the packaged material is wetted by water, the packaging film can adhere to the surface of this material. The inner and outer two-layer structure and the materials used in the film are the main structure and main materials of the film. When the inner and outer two-layer structure and the materials used are determined, if other materials are added as an intermediate layer between the inner layer and the outer layer, the intermediate layer plays a bonding function between the inner layer and the outer layer and should be regarded as a supplement to the present invention; if other materials are added as a new outer layer, the original outer layer is sandwiched between the new outer layer and the inner layer as an intermediate layer, which should be regarded as a supplement to the present invention.
[0023] Polyvinyl alcohol, a water-soluble material that is harmless to the human body, is selected as a bonding material. It is compounded with an environmentally friendly polyester-based fully biodegradable material by a melt extrusion method to form a biodegradable film with a double-layer structure. The inner layer is polyvinyl alcohol that has adhesive properties after being wetted, and the outer layer has no adhesive properties. This film has no stickiness in a dry state, and the inner layer has a certain degree of stickiness and self-adhesion in a wet state. It can adhere to the surface of common building materials in a watery state and is not easy to tear off after the water dries. The double-layer melt extrusion method can make the film thin and save costs. Epoxy modifiers and ethylene-acrylate-methacrylate glycidyl ester are added to the outer layer and the inner layer respectively, which improves the adhesion between the outer layer and the inner layer and makes it difficult to peel off. At the same time, the equipment and process of spraying glue are eliminated. The process is simple and environmentally friendly. The bonding material is non-toxic, water-soluble, and easy to remove. When the film is torn off from the material, even if a small amount of film or inner layer material remains on the packaged material, it can be washed away without leaving glue marks.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The fully biodegradable film of the present invention has the property of being wet and sticky, and can be used in the production and packaging of building materials such as tiles and glass. It fits tightly with the packaged materials, and the layers of the film are not easy to peel off. In the process of building materials production, the surface is generally washed with water at the end, and these building materials need to be dried. The film of the present invention can skip the drying link and directly use the film of the present invention for coating and packaging. Since the biodegradable materials used have high water permeability, the water in the package will evaporate quickly and will not remain in the package all the time, saving drying time and energy consumption. The adhesive of the packaging film of the present invention is water-soluble polyvinyl alcohol, which can be easily removed by washing with water after removing the package, does not require special chemical solvents to remove, is non-toxic and environmentally friendly, and reduces the risk of traditional adhesives being easily scratched and corroded during the removal process. The present invention can also be used as a wrapping film to wrap the goods, and then spray water on the surface of the last layer to achieve self-adhesion. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the peel strength test of the fully biodegradable film of the present invention. DETAILED DESCRIPTION
[0027] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] Experimental materials: Polybutylene adipate / terephthalate, A400 MF NC801, Zhuhai Jinfa Biomaterials Co., Ltd.; polylactic acid, 4032D, Natureworks; epoxy chain extender, ADR 4468 BASF AG; polyvinyl alcohol, 0588, Changchun, Taiwan, China; glycerol, analytical grade, Xilong Chemical; ethylene-acrylate-glycidyl methacrylate, LOTADERAX8900 Arkema, France; antioxidant, 1010, commercially available; antioxidant, 168, commercially available.
[0030] Preparation steps of fully biodegradable packaging film (Film A):
[0031] (1) 80 parts of poly(butylene adipate / terephthalate), 20 parts of poly(lactic acid) and an epoxy chain extender (accounting for 0.6% by weight of the outer layer raw material) are weighed, melt-blended in a twin-screw extruder, extruded into granules and dried to obtain an outer layer material;
[0032] (2) 80 parts of polyvinyl alcohol were weighed, mixed with 20 parts of glycerol, 0.2 parts of antioxidant 1010 and 0.2 parts of antioxidant 168 in a high-speed mixer, melt-blended in a twin-screw extruder, and the melt-blended product was mixed with 3 parts of ethylene-acrylate-glycidyl methacrylate in a high-speed mixer for 1 minute to obtain an inner layer material;
[0033] (3) The outer layer material of step (1) and the inner layer material of step (2) are respectively added into a double-layer extrusion film blowing machine, and the film is blown, the edges are cut, and the film is rolled up to obtain a packaging film.
[0034] Comparative Example 1
[0035] Referring to Example 1, the difference is that in step (1), low-density polyethylene is used as the outer layer material:
[0036] (1) Low-density polyethylene (linear low-density polyethylene, 7042, Maoming Petrochemical) was used as the outer layer material. Other steps were the same as in Example 1. The prepared film was Film B.
[0037] Comparative Example 2
[0038] Use transparent tape as film C (Wanrong).
[0039] Comparative Example 3
[0040] A point-break plastic wrap was used as film D (Miaojie).
[0041] Comparative Example 4
[0042] Referring to Example 1, except that in step (1), no epoxy chain extender was added, 80 parts of polybutylene adipate / terephthalate and 20 parts of polylactic acid were melt blended in a twin screw, extruded into granules and dried to obtain an outer layer material. The other steps were the same as in Example 1. The obtained film was used as Film E.
[0043] Comparative Example 5
[0044] Referring to Example 1, the difference is that in step (2), ethylene-acrylate-glycidyl methacrylate is not added, 80 parts of polyvinyl alcohol, 20 parts of glycerol, 0.2 parts of antioxidant 1010 and 0.2 parts of antioxidant 168 are fully mixed in a high-speed mixer, and melt-blended in a twin-screw extruder to obtain an inner layer material. The other steps are the same as in Example 1. The obtained film is referred to as Film F.
[0045] Comparative Example 6
[0046] Refer to Example 1, except that no epoxy chain extender is added in step (1), and no ethylene-acrylate-glycidyl methacrylate is added in step (2). The other steps are the same as in Example 1. The obtained film is referred to as Film G.
[0047] Example 2
[0048] Referring to Example 1, the difference is that the inner layer material in step (2) also contains 8 parts of polyester-based fully biodegradable material modified by an epoxy modifier, and the polyester-based fully biodegradable material modified by an epoxy modifier is the outer layer material in step (1) of Example 1. The preparation steps are as follows:
[0049] (2) 80 parts of polyvinyl alcohol were weighed by weight, mixed with 8 parts of the outer layer material of step (1), 20 parts of glycerol, 0.2 parts of antioxidant 1010 and 0.2 parts of antioxidant 168 in a high-speed mixer, and then melt-blended in a twin-screw extruder. The melt-blended product was mixed with 3 parts of ethylene-acrylate-glycidyl methacrylate in a high-speed mixer for 1 minute to obtain an inner layer material; the other steps were the same as in Example 1. The obtained film was referred to as Film H.
[0050] Example 3 Peel Strength Test
[0051] Experimental materials: Film A, Film B, Film C, Film D, Film E, Film F, Film G, and Film H in Examples 1-2 and Comparative Examples 1-6.
[0052] Experimental methods;
[0053] 1. Test method for peel strength between film A and surface wetting material:
[0054] Stick the inner layer of film A on the moistened surface of polished tile / frosted tile / glass / wood / iron / copper paperboard and let it stand for 1 day. Fix one end of the polished tile / frosted tile / glass / wood / iron / copper paperboard on the lower fixture of the stretching machine and the unbonded part of the film on the upper fixture of the stretching machine. Perform a peeling test at a stretching rate of 50 mm / min and record the maximum force.
[0055] The inner layer of film A is attached to the outer layer of another film A / film B with a moistened surface, and allowed to stand for 1 day. The unbonded part of the other end of the film is fixed to the upper and lower clamps of the stretching machine, and a peeling test is performed at a stretching rate of 50 mm / min, and the maximum force is recorded.
[0056] 2. Test method for peeling strength between film A and surface dry material:
[0057] Stick the inner layer of film A on the surface of a dry polished tile and let it stand for 1 day. Fix one end of the tile on the lower clamp of the stretching machine and the unbonded part of the film on the upper clamp of the stretching machine. Perform a peeling test at a stretching rate of 50 mm / min and record the maximum force.
[0058] 3. The peel strength test between film B and the polished ceramic tile with wetted surface is carried out in the same manner as above.
[0059] 4. The peel strength test between film C and polished ceramic tiles with wet surfaces and polished ceramic tiles with dry surfaces is carried out in the same manner as above.
[0060] 5. The peel strength test between film D and a polished tile with a dry surface and another film D with a dry surface is carried out in the same manner as above.
[0061] 6. The peel strength test between the inner layer of film E and the polished ceramic tile with a wet surface and another film E with a wet surface is carried out in the same manner as above.
[0062] 7. The peel strength test between the inner layer of film F and the polished ceramic tile with a wet surface and another film F with a wet surface is carried out in the same manner as above.
[0063] 8. The peel strength test between the inner layer of film G and the polished ceramic tile with a wet surface and another film G with a wet surface is carried out in the same manner as above.
[0064] 9. The peel strength test between the inner layer of the film H and the polished ceramic tile with a wet surface and another film H with a wet surface is carried out in the same manner as above.
[0065] The test results are as follows.
[0066] Table 1 Peel strength test
[0067]
[0068]
[0069] As can be seen from Table 1, the film A prepared in Example 1 of the present invention can be adhered to the surface of wetted articles, including ceramics, glass, cardboard, wood chips and other materials, and there is a certain peeling force between the film and the packaged articles. However, film A does not have such adhesion on the surface of dry articles. The difference in peeling force before and after wetting is helpful for packaging personnel to choose whether to adhere according to the actual needs of the packaged articles. It can be seen from the test results of film B that when PE (low-density polyethylene) is selected as the outer film, the film layer is easily separated from the inner film. It can be seen from the test results of film C that the present invention has similar adhesion to common tapes, but the glue on the tape is not sticky when wet. The wet adhesiveness of the present invention is essentially different from the adhesiveness of the tape. It can be seen from the test results of film D that the commercially available PE cling film is mainly self-adhesive and has almost no adhesion to other materials. From the test results of Film E and Film F, it can be seen that the films with epoxy additives added alone or ethylene-acrylate-glycidyl methacrylate added alone are prone to peeling between the inner and outer layers, resulting in reduced peel strength between the films and the packaging materials.
Claims
1. A fully biodegradable film, characterized in that: The invention has an inner and outer two-layer structure, wherein the outer layer is a polyester fully biodegradable material modified by an epoxy modifier; the inner layer is a mixed material, wherein the raw materials of the inner layer mixed material include 50-90% polyvinyl alcohol, 5-20% plasticizer, 1.5-8% ethylene-acrylate-glycidyl methacrylate, and the rest are other additives, which are selected from one or more of antioxidants, opening agents, and inorganic powder fillers. The alcoholysis degree of the polyvinyl alcohol is 78-99%, and the polymerization degree is 30,000-170,000.
2. The film according to claim 1, characterized in that The inner layer also includes polyester fully biodegradable materials modified by epoxy modifiers, which is no more than 30%.
3. The film according to claim 1 or 2, characterized in that The epoxy modifier-modified polyester fully biodegradable material is prepared by modifying the polyester fully biodegradable material with an epoxy modifier accounting for 0.4-0.8% of the raw material weight; the polyester fully biodegradable material is selected from one or two materials of polybutylene adipate / terephthalate, polylactic acid, polypropylene carbonate, polybutylene succinate, polyglycolic acid, and polycaprolactone.
4. The film according to claim 3, characterized in that The epoxy modifier is an oligomer with a molecular weight of 6000-8000 g / mol and an epoxy value of 200-400 g / mol.
5. The film according to claim 1 or 2, characterized in that: The alcoholysis degree of the polyvinyl alcohol is 78-88%.
6. The film according to claim 1 or 2, characterized in that: The plasticizer is glycerol or a compound plasticizer obtained by mixing glycerol with other plasticizers. The other plasticizers are selected from one or more of ethylene glycol, polyethylene glycol, triethylene glycol, and 1,3-propylene glycol.
7. The film according to claim 1 or 2, characterized in that: The weight proportion of glycidyl methacrylate groups in the ethylene-acrylate-glycidyl methacrylate is 6-10%.
8. The method for preparing a thin film according to any one of claims 1 to 7, characterized in that: The raw materials are heated, melted and co-extruded in multiple layers, and then the films are prepared by film blowing, casting and calendering.
9. The preparation method according to claim 8, characterized in that When the film is prepared by the film blowing method, the specific steps are as follows: (1) Weighing a polyester fully biodegradable material and an epoxy modifier by weight, melt-blending them in a twin-screw extruder, extruding them into granules, and drying them to obtain a polyester fully biodegradable material modified with an epoxy modifier as an outer layer material; (2) weighing raw materials, mixing polyvinyl alcohol, plasticizer and other additives in a high-speed stirrer, melt-blending them in a twin-screw extruder, and then mixing them with ethylene-acrylate-glycidyl methacrylate at room temperature at high speed to obtain an inner layer material; Alternatively, the raw materials are weighed by weight, polyvinyl alcohol, the polyester-based fully biodegradable material modified by the epoxy modifier obtained in step 1), a plasticizer and other additives are fully mixed in a high-speed mixer, melt-blended in a twin-screw extruder, and then mixed with ethylene-acrylate-glycidyl methacrylate at room temperature at high speed to obtain an inner layer material; (3) The outer layer material and the inner layer material are respectively added into a double-layer extrusion film blowing machine, and the film is blown, the edges are cut, and the film is rolled to obtain a packaging film.
10. Use of the film according to any one of claims 1 to 7 in building materials, characterized in that: The inner layer of the film faces the building material and is in direct contact with the building material.
Citation Information
Patent Citations
Completely-biodegradable film bag material and preparation method of film bag
CN109810476A
Biodegradable composite modified film bag particle material and preparation method thereof
CN113773559A
Biodegradable resin film or sheet excellent in hydrolysis resistance
JP2004010693A
Water-responsive biodegradable polymer compositions and method of making same
US20020193517A1
Degradable high-barrier composite film and preparation method therefor
WO2023115599A1